The 3rd International Conference on Advances in Mechanical Engineering - Khan, Muhammad; Hyder, Mohammad; Irfan, Muhammad; Masud, Manzar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The 3rd International Conference on Advances in Mechanical Engineering 2023 (ICAME-23) was organized on 24th August 2023 by the Department of Mechanical Engineering, Capital University of Science and Technology (CUST). All the articles are single-blindfold reviewed. The acceptance rate of the conference was 65%. ICAME is held annually and welcame high-quality theoretical and empirical original research papers, case studies, and review papers from researchers, academicians, professionals, practitioners, and students worldwide. ICAME-23 accepted research papers in the discipline of: Experimental and Computational Fluid Dynamics; Thermodynamics and heat transfer analysis; Machine and Mechanisms; Design and Solid Mechanics; Manufacturing, Production and Industrial Engineering; Engineering and Technology Management; Renewable Energy and Environmental Engineering; Bioengineering; Materials and Failure Analysis; Other Related Fields. The ICAME-23 conference provided a platform for the national and international speakers/participants to present their state-of-the-art research work to diverse audiences from academia and industry. The conference proceedings are published in the Engineering Proceeding of MDPI, Switzerland. All the articles are individually indexed and are citable via Digital Object Identification (DOI).